Analisis Semantik pada Puisi Kangen Karya WS Rendra - Najwa Fasyah; Intan Christine Nainggolan; Novia Marissa Valerina Pardosi; Yati Virma Saragih (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study analyzes the semantic meaning in the poem "Kangen" by W.S. Rendra. Semantics is the study of meaning in language, encompassing lexical and grammatical meanings. Poetry, as a form of the poet's expression, often uses figurative language that requires deep understanding. This analysis employs a qualitative descriptive method to explain the meanings contained in the poem. Data is collected through literature study and analyzed using data reduction, data presentation, and conclusion drawing approaches. The results indicate that the poem "Kangen" is rich in complex emotional and aesthetic meanings. The use of repetition and figures of speech in the poem strengthens the expression of longing and enriches the reader's experience. This semantic analysis helps readers understand the poem's meaning and structure more deeply.